Heterogeneous Mercury Oxidation on Au(111) from First Principles - Lim, Dong-Hee; Wilcox, Jennifer (American Chemical Society, 2013)
Density functional theory (DFT) studies of mercury oxidation on Au(111) are conducted to determine the potential Hg oxidation mechanisms taking place on catalytic gold surfaces by using the Perdew and Wang approximation (PW91) described by a generalized gradient approximation (GGA). The Hg oxidation was examined via a Langmuir Hinshelwood mechanism where each Hg and Cl-2 (or HCl) species is separately adsorbed on the gold surface and the bimolecular reaction occurs through the formation of bound HgCl and . For this, the Climbing Image-Nudged Elastic Band (CI-NEB) method has been employed to calculate the activation energies of HgCl and HgCl2 formation pathways. In the three-step Hg oxidation mechanism (Hg -> HgCl -> HgCl2), the second Cl attachment step is endothermic which is the reaction rate-limiting step, while the first Cl attachment step is exothermic. This observation implies that Hg oxidation prefers a pathway in which HgCl and HgCl2 are formed, rather than a pathway directly oxidizing Hg to HgCl2. In the presence of H atoms due to HgCl dissociation on the Au surface, the H atoms lower the activation energy for Hg oxidation by consuming the electron charge of Au atoms, thereby weakening the strength of interaction between Cl and the Au surface and lowering an energy required to detach Cl from the Au surface. This mechanism is in the absence of site competition on the Au surface. In addition, details of the electronic properties of these systems are discussed.